(3ehUd GdWdGH Edi bhGYO GdEYQGHs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3LeGd GdOjf CHh eMeO YHO Gddg jhSa Hf gTGes
(3ChdgG (B:s
(3GdMeO ddg Gdedge GdMeOg hHYO ajbhd NGdO Hf YHO Gddg GdCRgQi gPG TQM dWja Ydi bhGYO GdEYQGH SejJg ehUd GdWdGH Edi bhGYO GdEYQGH HSe Gddg GdQMef GdQMje GdHGA eJYdbI HaYd eMPha JbOjQg CaJJM s
(3BNQgG (B:s
(3ef GddZh GdHGWd hcdGe Gddg efRg Yf Pdc hai gPG GdbOQ GdPi PcQI caGjI def JCedg MjK bGd JbJai HeJCedgG LGOI GdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG SDGd ai bhdg Ndb Gddg GdSeGhGJs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs